Capnia shasta, a new species in the Californica Group from northwestern California (Plecoptera, Capniidae) - Nelson, Charles Riley (Illiesia, 2009)
The genus Capnia contains 56 species in North America and approximately 150 species worldwide. A past phylogenetic analysis of the Californica Group revealed two major subgroups. From that analysis and reviewing of pertinent specimens, the Californica Subgroup includes a new species that is herein described. Capnia shasta is unique in that it is the only member of the Californica Group in which males have tergal knobs only on segment 9 and has no distinctively divided process on the epiproct. Females are not reliably identified to species in the absence of males. We ran a branch and bound analysis using a corrected matrix based on the published analysis. Our analysis yielded six equally parsimonious trees. In all of these trees the topology conformed with the previously published tree, but with Capnia shasta joining the tree in a polytomy when a consensus tree was produced. Capnia shasta is currently known from a single locality on a single date from a smalltributary of the Sacramento River. We suggest that further careful wintercollections of many sites in the area are warranted. The limited distribution of C. shasta points to careful conservation of the tributaries ofthe Sacramento River.
Keywords: entomologija; entomology; Plecoptera; vrbnice; Capniidae; nove vrste; Kalifornija; Capnia shasta; California; USA